Survei Manajemen Perwasitan Sepakbola Di Askab Banyumas Tahun 2022 (Universitas Negeri Semarang, 2022)
The background of the research is due to the unequal distribution of refereeing tasks, little competition, many work programs that are not implemented, and organizational governance. The purpose of this study was to describe the management of football refereeing in Askab Banyumas in 2022. The type of research was a survey with a qualitative descriptive approach. Methods of data collection using observation, interviews, and documentation. The targets of this research are the chairperson, the refereeing bureau, and the Askab referee. The analysis of this research uses data reduction, data presentation, and conclusion drawing. The results showed that (1) the planning function there was already a vision, mission, and goals (2) The organizing function there was an organizational structure that divided the duties of each member in detail and the coordination mechanism well. (3) The actuating function the chairman, referee bureau, and referees carry out their duties properly (4) The controlling function the chairman and referee bureau go directly to the field to review the referee's performance. The conclusions of this study were (1) Planning for refereeing went quite well (2) Organizing refereeing went well (3) The actuating of referees was said to be quite good (4) Controlling of refereeing was going well.